Consolidation of Viscoelastic Soil With Vertical Drains for Continuous Drainage Boundary Conditions Incorporating a Fractional Derivative Model - Chen, Peishuai; Li, Jiacheng; Huang, Minghua; Li, Dejie (Frontiers in Materials, 2021)
In geotechnical engineering, the vertical drain is the most economical method for accelerating the consolidation of large-area soft ground. Considering the viscoelasticity of the soil and the actual drainage conditions on the top of the soil, this study introduces continuous drainage boundary conditions and adopts a fractional derivative model to describe the viscoelasticity of the soil. Using this viscoelastic model, the governing partial differential equation of vertical drains under continuous drainage boundary conditions is obtained. With the application of the Crump numerical inversion method, the consolidation solution of vertical drains is obtained. Further, the rationality of the proposed solution is verified by several examples. Moreover, some examples are provided to discuss the influence of the interface drainage parameters on the top of soil and the viscoelastic parameters of soil on the consolidation behavior of the vertical drains. The proposed method can be applied to the fields of transport engineering to predict the consolidation settlement of the foundation reinforced by vertical drains.